PEMISAHAN FAT, OIL, AND GREASE (FOG) DARI LIMBAH FOODCOURT DENGAN DISSOLVED AIR FLOTATION - Bayu Satria Utama; Maria E. Simorangkir; I Nyoman Widiasa (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Oil waste water is the source of pollution that is often found in everyday life. Oil as a pollutant that is contained in the water must be separated so that oil can be utilized, and its existence as a pollutant can be removed. In this research study will be conducted to find the most suitable parameters of the pressure to separate the fat, oil, and grease from waste water foodcourt with Dissolved flotation. The variables used in the separation pressure is 4.5; 5; 5.5; and 6 bar. Separation results obtained will be analyzed by using analysis of total suspended solids. Data analysis results obtained are total suspended solids in the feed of 40,000 mg / L, after the water is separated using flotation Dissolved respectively obtained at a pressure of 4.5 bar total suspended solids of 3000 mg / L, at a pressure of 5 bar can get the total solids suspension of 2500 mg / L, at a pressure of 5.5 bar total suspended solids obtained at 1500 mg / L, and at a pressure of 6 bar obtained total suspended solids of 500 mg / L.